Validation of a subjective global assessment questionnaire - Maiara Pires Carniel; Daniele Santetti; Juliana Silveira Andrade; Bianca Penteado Favero; Tábata Moschen; Paola Almeida Campos; Helena Ayako Sueno Goldani; Cristina Toscani Leal Dornelles (Elsevier, 2015)
Objective: To validate the Subjective Global Nutritional Assessment (SGNA) questionnaire for Brazilian children and adolescents. Methods: A cross-sectional study with 242 patients, aged 30 days to 13 years, treated in pediatric units of a tertiary hospital with acute illness and minimum hospitalization of 24 h. After permission from the authors of the original study, the following criteria were observed to obtain the validation of SGNA instruments: translation and backtranslation, concurrent validity, predictive validity, and inter-observer reliability. The variables studied were age, sex, weight and length at birth, prematurity, and anthropometry (weight, height, body mass index, upper arm circumference, triceps skinfold, and subscapular skinfold). The primary outcome was considered as the need for admission/readmission within 30 days after hospital discharge. Statistical tests used included ANOVA, Kruskal-Wallis, Mann-Whitney, chi-square, and Kappa coefficient. Results: According to SGNA score, 80% of patients were considered as well nourished, 14.5% moderately malnourished, and 5.4% severely malnourished. Concurrent validity showed a weak correlation between the SGNA and anthropometric measurements (p < 0.001). Regarding predictive power, the main outcome associated with SGNA was length of admission/readmission. Secondary outcomes associated included the following: length of stay at the unit after SGNA, weight and length at birth, and prematurity (p < 0.05). The interobserver reliability showed good agreement among examiners (Kappa = 0.74). Conclusion: This study validated the SGNA in this group of hospitalized pediatric patients, ensuring its use in the clinical setting and for research purposes in the Brazilian population. Resumo: Objetivo: Validar o questionário de Avaliação Nutricional Subjetiva Global (ANSG) para a população de crianças e adolescentes brasileiros. Métodos: Estudo transversal, realizado com 242 pacientes, de 30 dias a 13 anos, atendidos em unidades pediátricas de um hospital terciário, com doenças agudas e tempo de permanência mínima de 24 horas hospitalizados. Após autorização dos autores do estudo original foram realizadas as seguintes etapas para obtenção da validação dos instrumentos de ANSG: tradução (backtranslation), validade de critério concorrente e preditiva e confiabilidade interobservador. As variáveis em estudo foram: idade, sexo, peso e comprimento ao nascer, prematuridade e antropometria (peso, estatura, índice de massa corporal, circunferência braquial, dobra cutânea tricipital e dobra cutânea subescapular). O desfecho principal considerado foi necessidade de internação/reinternação até 30 dias após a alta hospitalar. Os testes estatísticos utilizados foram: ANOVA, Kruskal-Wallis, Mann-Whitney, Qui-quadrado e coeficiente Kappa. Resultados: De acordo com a classificação do ANSG 80% dos pacientes foram classificados como bem nutridos, 14.5% moderadamente desnutridos e 5.4% gravemente desnutridos. A validade concorrente mostrou fraca a regular correlação do ANSG com as medidas antropométricas utilizadas (p < 0.001). Quanto ao poder preditivo, desfecho principal associado ao ANSG foi tempo de internação/reinternação. Os desfechos secundários associados foram: tempo de permanência na unidade após ANSG, peso e comprimento ao nascer e prematuridade (p < 0.05). A confiabilidade interobservador mostrou boa concordância entre os avaliadores (Kappa = 0.74). Conclusão: Este estudo validou o método de ANSG nessa amostra de pacientes pediátricos hospitalizados, possibilitando seu uso para fins de aplicação clínica e de pesquisa na população brasileira. Keywords: Nutritional assessment, Children, Adolescents, Anthropometry, Validation studies, Palavras-chave: Avaliação nutricional, Crianças, Adolescentes, Antropometria, Estudos de validação